Inflation Smoothing and the Modest Effect of VAT in Germany - Danninger, Stephan; Carare, Alina (Washington, D.C. : International Monetary Fund, 2008)
Increases in German core inflation following the 2007 VAT hike were smaller than expected, leading to speculation about delayed inflationary effects. This paper argues to the contrary that price increases in advance of the VAT hike explain the small increase upon implementation. We find that core inflation rose by 0.36 percentage point in the run up and by a further 0.40 percentage point at the time of the VAT hike. Cumulatively, the tax hike contributed to two thirds of the increase in core inflation in 2006-07 at an estimated pass-through of 73 percent. Most of the increase in 2006 was of general nature, while about one sixth can be attributed to durable goods and items with low degree of competition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet